How Much Does It Cost? A Simulation-Based Method for Cost Prediction in Systems-of-Systems Acquisition Processes - Graciano Neto, Valdemar V.; Horita, Flávio E. A.; dos Santos, Rodrigo P.; Viana, Davi; Kassab, Mohamad (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2018: Anais do III Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2018)
Software economics, acquisition, and pricing are important concerns, in particular for Systems-of-Systems (SoS). SoS are alliances of independent software-intensive systems combined to offer holistic functionalities as a result of the constituents interoperability. SoS engineering involves separately acquiring constituents and combining them to form the SoS. Despite the existence of cost prediction techniques at Systems Engineering practice, predicting SoS acquisition costs at design-time should include: 1) an analysis of the minimum set of constituents that offer a ‘good enough’ result, and 2) an analysis of the compatibility between the constituents to deliver the expected result. The main contribution of this paper is proposing a novel simulation-based method for cost prediction in constituents acquisition process, while considering the effectiveness of constituents combination to offer the intended functionalities, and predicting the lowest configuration, at design-time. We adopt a simulation model to predict, at design-time, the results that shall be yielded by the constituents during SoS operation. Preliminary results point out the success of our method to predict such costs while still supporting a selection of the best architectural configurations.